(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In spite of the many investments in information technology (IT) applications in the industry, the reports show that some users do not use it despite the access to accounting technologies and information systems. Here, perceived reliability, confidence, and security are the key components that affect the use of these systems. Hence, the purpose of the present study was to determine the effect of objective aspects, such as electronic data exchange processes, technical protections, and security statements on using accounting information systems and the exploitation of the three mental aspects of security, assurance, and perceived reliability among the customers of Assaluyeh petrochemicals. The method nature was survey-applied. The study data was collected using a survey of petrochemical customers in Assaluyeh through a questionnaire. Structural validity was studied using confirmatory factor analysis with Cronbach’s alpha coefficient greater than 0.7 for the various constructs of the questionnaire confirming the assurance. Statistical data analysis was done in warp pls software and spss 18 software. The findings indicated that the structural model of the study had sufficient predictive power. In other words, 43.7% of the variance of the perceived security was explained by the variables entered, 30.4% of the changes in perceived reliability by the variable entering it in the model (objective aspects and perceived security) as well as 25.9% of the changes in using the accounting information system by two variables (assurance and reliability) and perceived security.